On the Conceptuality of Counselor’s Image in Epic Monuments of Medieval Literature (T.Melory, “The Death of Arthur” and Lo Guanchjun, “Romance of the Three Kingdoms”) - Gonchar-Khanjyan, Natalya (Bulletin of Yerevan University B: Philology, 2022)
In the modern world, we are dealing with the institution of the counselor, set in the system of state structure. The  level of  hierarchical and functional structurating of this state institution, its ranking, detailing by competences are conditioned by the development of the state, its goal-setting and scale in the domestic and foreign policy. In the light of the processes, trends and institutions operating in the world nowadays, the appeal to historical and  literary monuments of the past, reflecting facts and figures, stories, contents and concepts which correlate as deep roots with the content and concepts of today's life, becomes more relevant. From this point of view, the author’s observations concerning the role and specific features of the figure of the counselor in the two outstanding monuments of medieval literature examined — English and Chinese — may be of some interest. The observations on these monuments should take into account their genre character, belonging to different literary traditions: the European chivalric romance (The Death of Arthur), and the Chinese historical novel (Romance of the Three Kingdoms), which is reflected in their different ratio of historical-real and fictional-fantastic components.
Keywords: State; politics; counselor; medieval literature; The Death of Arthur; Romance of the Three Kingdoms; concept; purpose; means